Esporte como experiência estética e educativaEsporte educativa: uma abordagem fenomenológica - Silva, Liege Monique Filgueiras da (2014)
This paper deals with sport as a possibility of disclosing the sensible, and defends the idea that being a sportsperson equals living an aesthetic and educative experience in which one can interacts with the sensible by the athletic body s reverberation of sensations in the dimension of the experienced. We try to answer, in our work, basically three questions: what moves the athlete when practicing a sport? Which are the meanings and motivations for the practice of sports? At what measure the athlete s experience gains an educational character? Sport is debated in this work as an extension of the living, as long as it tries to understand the meanings inherent to sport itself as well as to the sportive experience as a kind of education. In support of our argument, we give a theoretic and philosophical approach to our thesis, based on thinkers like Maurice Merleau-Ponty, Walter Benjamin, Marcel Mauss and Friedrich Schiller. For this purpose, we get support on the phenomenology of the French philosopher Maurice Merleau-Ponty. Our reference is the living world of the athlete and his experience as a field of the sensible. Our point of departure is the analysis of the narratives of sport experiences, including five aesthetic elements; time and space of the body in the sports courts; the look on the sportive context; the contact with the adversary; victory and defeat; the technical gesture. Besides it, we worked out an aesthetic evaluation of the movies Olympia and Invictus , what let us discuss three thematic categories: sensibility, emotions and the play paradox. Subsequently, we point sport as an optimizer of the sensible education, present on the body s processes, like the body in movement. It was also made clear along this paper that we tried to accomplish an analysis on sports centered in the athlete s body as an outfit of the senses to things related to the sensible, whose aesthetic experience overpasses any deterministic conception that should sum up the sportive world to mercantilization, discipline practices and mechanicism. This approach franchises gateways to a Physical Education which, containing sports as one of its support, let pupils enjoy the pleasure of constructing common objectives, incorporating the capacity of replicating, re-making and playing as a field of possibilities offered by an education characterized as being moving, sensible and fitful to a body in movement